Association of Neighborhood Socioeconomic Context With Participation in Cardiac Rehabilitation. Issue 10 (11th October 2017) - Bachmann, Justin M.; Huang, Shi; Gupta, Deepak K.; Lipworth, Loren; Mumma, Michael T.; Blot, William J.; Akwo, Elvis A.; Kripalani, Sunil; Whooley, Mary A.; Wang, Thomas J.; Freiberg, Matthew S.
Abstract : Background: Cardiac rehabilitation (CR) is underutilized in the United States, with fewer than 20% of eligible patients participating in CR programs. Individual socioeconomic status is associated with CR utilization, but data regarding neighborhood characteristics and CR are sparse. We investigated the association of neighborhood socioeconomic context with CR participation in the SCCS (Southern Community Cohort Study). Methods and Results: The SCCS is a prospective cohort study of 84 569 adults in the southeastern United States from 2002 to 2009, 52 117 of whom have Medicare or Medicaid claims. Using these data, we identified participants with hospitalizations for myocardial infarction, percutaneous coronary intervention, or coronary artery bypass surgery and ascertained their CR utilization. Neighborhood socioeconomic context was assessed using a neighborhood deprivation index derived from 11 census‐tract level variables. We analyzed the association of CR utilization with neighborhood deprivation after adjusting for individual socioeconomic status. A total of 4096 SCCS participants (55% female, 57% black) with claims data were eligible for CR. CR utilization was low, with 340 subjects (8%) participating in CR programs. Study participants residing in the most deprived communities (highest quintile of neighborhood deprivation) were less than half as likely to initiate CR (odds ratio 0.42, 95% confidence interval, 0.27–0.66, P <0.001) as those in the lowest quintile. CR participation was inversely associated with all‐cause mortality (hazard ratio 0.77, 95% confidence interval, 0.60–0.996, P <0.05). Conclusions: Lower neighborhood socioeconomic context was associated with decreased CR participation independent of individual socioeconomic status. These data invite research on interventions to increase CR access in deprived communities.